ANALISIS RISIKO KERJA PADA PROYEK PEMBANGUNAN BANDARA - Stephanie Almeyda; I Nyoman Dita Pahang Putra (Racic : Rab Construction Research, 2024)
Risk is an event that results in both physical and material losses. Companies involved in a project development must implement an occupational safety and health program. Although it cannot be denied that there are still some work accidents caused by various factors, so this research aims to analyze the risk of work accidents on the project. Risk analysis in this study was carried out using two methods. In the first method, it is necessary to identify the types of work accidents using the Hazard Identification and Risk Assessment (HIRA) method, starting with a survey in the form of distributing questionnaires to respondents to find out the value of severity and probability for each variable so that the biggest risk is known. After being identified, 6 major risk variables were obtained and one of them, namely in the mobilization/demobilization activities of heavy equipment and material vehicles, was identified as having a structural loading hazard with the worst work accident being a dump truck mired when crossing a structure that could not withstand the load. After finding the hazard with the greatest risk, the causal factors of the risk were then sought using the second method, namely, Fault Tree Analysis (FTA) where the risk was caused by 3 factors, namely human factors, management factors, and environmental factors. 11 basic causes were found with a minimum cut set combination resulting in 7 basic cause combinations (basic events).Keywords: Risk Analysis, Hazard Identification and Risk Assessment, Fault Tree Analysis